A longitudinal study of aphasia due to pure sub-cortical strokes - Durjoy Lahiri; Alfredo Ardila; Souvik Dubey; Biman Kanti Ray (Annals of Indian Academy of Neurology, 2020)
Introduction: Contemporary neuro-imaging techniques have significantly advanced our understanding of the brain organization of language and the involvement of subcortical areas in aphasia. However, articles on sub-cortical aphasia, particularly in non-western languages, remain to be few and far between. We set out to explore aphasia typology in sub-cortical strokes among Bengali-speaking population with a focus towards providing a longitudinal view over a period of 3 months post-stroke. Methods: Bengali version of Western Aphasia Battery (BWAB) was used to assess and classify language dysfunction in our study participants. Conventional brain imaging techniques (CT scan & MRI) were used to detect and localize strokes. Uni-variate analysis for categorical variable (location versus aphasia typology) was performed using Chi square and Fischer's exact test (as applicable). Directional measures were calculated using lambda and Goodman-Kruskal tau (Range of -1 to + 1). Boot strapping was applied while calculating the directional measures because of inadequate numbers in some sub-sections the sample. Results: Frequency of sub-cortical aphasia was observed to be 29.80% (62/208) in the index study. Four location of strokes were associated with language dysfunction, of which putamen (53.23%) was the commonest followed by striato-capsular region (33.87%). Thalamus and peri-ventricular white matter (PVWM) strokes (6.45% each) were infrequent in our sample of sub-cortical aphasia. Global aphasia (30/62, 48.38%) was the most frequent type observed in acute phase while Broca's aphasia (23/53, 43.39%) dominated among the follow up cases. Aphasia recovery (with follow up AQ of 90.0 or more) was observed in 12 (22.64%) patients of whom majority (8/12) had striato-capsular strokes. Conclusion: The present paper illustrates the epidemiological aspects as well as longitudinal course aphasia following pure sub-cortical strokes.